(untitled) (Al-Academy, 2017)
The research is aimed at dynamics the dynamics of the artistic form within the theater and the dynamics of this movement in the development of the form and the multiplicity of meaning. This research came to address a problem of great importance in the creation of the image and the form of theatrical presentation. The evolution and transformation within the display system requires a dynamic structure that enables the form of growth and growth. The aim of the research was to identify the dynamics of form in the Iraqi theater. The researcher then identified two terms: form and motor.In the theoretical framework, it was divided into two sections: the first (the dynamics of the artistic form) and the second (the dynamics of the act of directing in the theatrical presentation). Then the researcher chose a purposeful sample for the purpose of analysis, which is a play (the eighth day of the week), after which he reached the results of the research, which include: Kinetic does not know static form fixed in theatrical presentation, but are moving paths in which the model moves from one form to another. And then a list of margins and sources of research and then a summary in English